The Role of Human Resources, Competencies And Training In Nawacita Mediation In Improving The Performance of Balinese Lontar Craftsmen (IKM) In The District Karangasem Bali Province - I Ketut Merta; I Made Arya Pering; I Gusti Ayu Kumudawati (Return : Study of Management, Economic and Bussines, 2024)
This study aims to examine the Role of Human Resources, Competence and Training in Nawacita Mediation in Improving the Performance of Balinese Lontar Craftsmen (IKM) in Karangasem Regency, Bali. The theory used is Human Resource Management (MSDM) quantitative research method using a questionnaire with 50 samples and eight hypotheses assisted by data processing using SPSS version 24 and SEM_PLS. The results of the study 1. Human Resources have a significant positive effect on the performance of palm-palm craftsmen, 2. Competence has a significant positive effect on the performance of palmyra palm craftsmen, 3. Training has a positive but not significant effect on the performance of palm-palm craftsmen, 4. Nawacita has a significant positive effect on the performance of palm-leaf craftsmen, 5. Human Resources has a positive and not significant effect on nawacita, 6. Competence has a positive and insignificant effect on nawacita, 7. Training has a positive and insignificant effect on nawacita, 8. Nawacita is unable to mediate Human resources, Competence and training positively significantly to the performance of craftsmen. The implication shows that the performance of Lontar Producers can be explained by Human Resources, Competence and training and Nawacita is very high.